Cultural participation in Europe: shared problem or shared problematisation?. Issue 1 (2nd January 2017) - Stevenson, David; Balling, Gitte; Kann-Rasmussen, Nanna
Abstract : Europe has a 'problem'; it is becoming a 'less cultural continent' as fewer Europeans are 'engaging in cultural activities'. This conclusion has been reached due to the findings of the latest cross national cultural participation survey. This paper questions the existence of this 'problem' and instead suggests that there is a shared problematisation across Europe sustained by common discursive archaeology that employs various discursive strands in relation to a dominant institutional discourse. The argument is that the 'problem' of 'non-participation' legitimates a 'solution' that predates its emergence: the state subsidy of arts organisations. The paper recaps the comparable problematisations that the researchers have previously identified in the policy texts of their respective countries. It progresses to consider three distinct but interwoven discursive strands upon which the problem representation in both countries, and potentially across Europe, appears to rely.